2020
DOI: 10.1111/ppc.12520
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an expert mental health consumer research group: Perspectives of nonconsumer researchers

Abstract: Purpose: To explore the views and opinions of nonconsumer researchers to the concept of an Expert Consumer Researcher Group. Design and Methods: Qualitative exploratory involving individual interviews with nonconsumer mental health researchers experienced in working collaboratively with consumer researchers. Data were analyzed thematically. Findings: Participants viewed the concept positively, albeit with caution. Perceived advantages included: greater visibility and enhanced access; collegiality; sharing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
(144 reference statements)
0
5
0
Order By: Relevance
“…erefore, we need to clarify the connotation of the healthy personality of the employees. Healthy personality is a good character, which includes no aggressive personality, no violence, sincerity, and good treatment, which makes the employees of enterprises have a more ideal personality [18][19][20][21]. In order to analyze the mental health and consumption behavior of enterprise employees, it is necessary to analyze the definition of the healthy personality and the constitution of the healthy personality of the employees.…”
Section: Analysis On the Construction Of Healthy Personalitymentioning
confidence: 99%
“…erefore, we need to clarify the connotation of the healthy personality of the employees. Healthy personality is a good character, which includes no aggressive personality, no violence, sincerity, and good treatment, which makes the employees of enterprises have a more ideal personality [18][19][20][21]. In order to analyze the mental health and consumption behavior of enterprise employees, it is necessary to analyze the definition of the healthy personality and the constitution of the healthy personality of the employees.…”
Section: Analysis On the Construction Of Healthy Personalitymentioning
confidence: 99%
“…EBE need support to receive equal opportunities for professional development, appropriately flexible working arrangements and autonomy over the material they deliver and ideas that they present (Happell & Roper, 2007). A particular challenge is that, as the value of the input of EBE’s becomes more widely appreciated through an institution and/or a community, the demands on their time and resource increases without necessarily being reflected in the formal scope of the role (Happell, Gordon, et al, 2021). The EBE, due to their role being both professional and personal, often goes above and beyond what is contractually required of them, without being recognized for their efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies noted that researchers found engagement to be valuable and rewarding, 35,37,42,44,45,65,[67][68][69] giving them a deeper understanding of the research topic and lived experience perspectives. 43,44,47,54,56,70 Researchers also found that engagement added value to their research, 35,44,47,62,[71][72][73][74] brought a new perspective to the research project, 38,44,49,65,69 and was a valuable means of bringing about change in research. 75 In three studies, researchers reported finding lived experience as an irreplaceable expertise.…”
Section: Impact On People With Lived Experience (N = 35)mentioning
confidence: 99%
“…Time constraints; 37,42,53,62,[65][66][67]71,72,76,80,87,92 limited funding and financial resources; 32,37,48,57,62,[65][66][67]72,75,77,80,91 reliance on one organization 43 External partnerships; 35,43,48,50,54,55,57 networks and more resources available; 65,91 establishing a lived-experience researcher group; 73,74 support from organization; 62,65,92 support from funders; 62,77,91 incentives for engagement 77 (Continues)…”
Section: Resourcesmentioning
confidence: 99%
See 1 more Smart Citation